Prediction of Novel Bioactive Compound from Zingiber officinale as Non-nucleoside Reverse Transcriptase Inhibitors (NNRTIs) of HIV-1 through Computational Study - Kharisma, Viol Dhea; Septiadi, Luhur; Syafrudin, Syafrudin (Future Science, 2018)
Human immunodeficiency virus 1 (HIV-1) is one of the viruses of that causes AIDS in humans and disease outbreaks in this modern era. Reverse transcriptase (RT) enzyme though to be the functional enzyme that play a role on the HIV-1 virus replication. Bioactive compounds contained on Ginger (Zingiber officinale) is known to inhibit viral replication. This study aims to determine the alternative bioactive compounds contained on Ginger (Zingiber officinale) as as a non-nucleoside reverse transcriptase (NNRTIs) HIV-1 inhibitors through computational study. The reverse transcriptase (RT) enzyme model was retrieved from protein sequence database (PDB) and validated with Ramachandran Plot and the compound contained on Ginger was retrieved from database. Analysis of molecular docking, performed using PyRx and the interactions between Reverse Transcriptase (RT) enzyme of HIV-1 virus and Zingiber officinale active compound was analyzed by PyMol and LigPlot+, also the drug-likeness molecule properties with The Lipinski Rule’s of Five. From 24 active compound which have been docked, ?-sitosterol proven to be the most potential bioactive compound as inhibitors of Reverse Transcriptase (RT) enzyme because it has more negative binding energy and the same amino acid residue with the control. Therefore, ?-sitosterol is predicted to be used as non-nucleoside reverse transcriptase (NNRTIs) HIV-1 inhibitors.